Tinjauan UU No. 35 Tahun 2014 Tentang Perlindungan Anak Dan Hadits Hr. Bukhari Dan Muslim Mengenai Perundungan Di Kalangan Remaja - Muhammad Zahran Al Gibran; Tajul Arifin (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Adolescence is a crucial period in life where individuals develop their identity, values, and aspirations for their future. In this paper, we explore the various hopes held by adolescents for their future. From quality education to mental well-being, from satisfying careers to meaningful relationships, and from social contributions to financial stability, these hopes reflect their desires for a better and more meaningful life. We highlight the importance of understanding and supporting these hopes in shaping policies, programs, and practices that enable adolescents to reach their full potential and make positive contributions to society.